Study antimicrobial properties of hemp materials modified by copper nanoparticles - B. R. Tausarova; A. M. Sharipbek (Алматы технологиялық университетінің хабаршысы, 2021)
Optimal conditions for the processing of hemp materials with copper nanoparticles have been developed. The antibacterial properties of hemp materials modified by copper nanoparticles have been investigated. It has been shown that hemp materials modified by copper nanoparticles have antibacterial activity to bacteria and mold fungi E-Coli, Pennicillium brevi.